Effects of exposure to cement dust on hemoglobin concentration and total count of RBC in cement factory workers - Ahmad, Rahnuma; Akhter, Qazi Shamima (Journal of Bangladesh Society of Physiologist, 2018)
Background : Cement factory workers are exposed to cement dust during their daily work activities. Chronic exposure to cement dust may have adverse effect on the haemopoietic system and the workers would suffer from anemia that may lead to cardiovascular disease. Objective: To assess the effects of exposure to cement dust on hemoglobin concentration and total count of RBC in cement factory workers. Methods : This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2017 to June 2018. After fulfilling the ethical consideration, 46 apparently healthy male cement factory workers, working in a cement factory for 2 years or more, with age ranging from 20 to 50 years were study group and 46 age, BMI and socioeconomic condition matched apparently healthy male subjects from different areas of Dhaka city were control group. Hemoglobin concentration and total count of RBC were estimated using automated haematology analyzer. For statistical analysis, Unpaired Student’s ‘t’ test and Pearson’s correlation coefficient test were performed. Results: In this study, hemoglobin concentration and total count of RBC were significantly (p < 0.05) lower in study group than those of control group. Hemoglobin concentration was negatively related with duration of cement dust exposure. Conclusions: This study concludes that the cement dust exposure had deleterious effect on hemoglobin concentration and total count of RBC and the duration of exposure to cement dust had an impact on hemoglobin concentration. J Bangladesh Soc Physiol. 2018, December; 13(2): 68-72